Ang Ilokos, ang Ilokano ([Quezon City] Institute for Filipino Cinema, 1991)
Presents the three provinces of Northern Luzon - La Union, Ilocos Sur, and Ilocos Norte focusing on the peculiarity of the Ilocano.
VHS
Keywords: Churches -- Philippines -- Ilocos Norte; Churches -- Philippines -- Ilocos Sur; Philippine history; Geography